2004
DOI: 10.21273/hortsci.39.4.853c
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Applied Strontium as a Tracer for Calcium Transport in Apple Trees

Abstract: A field experiment was conducted at the Horticultural Research Center in Chanhassen, Minn. to help refine recommendations for use of calcium (Ca) sprays to reduce the incidence of bitter pit in `Honeycrisp' apple. Specific objectives were to: evaluate the amount of translocation from leaves to fruit using strontium (Sr) as a tracer for potential Ca movement, determine whether there are differences in translocation in early vs. later phases of fruit development, and evaluate the effect of an experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that Ca 2+ and Sr 2+ behave similarly in the biosphere and that most plants cannot discriminate between them at their biospheric concentrations (Watanabe et al 2007(Watanabe et al , 2016Drouet and Herbauts 2008;Burger et al 2019b). Therefore, Sr 2+ has been used as a long-and short-term tracer of Ca 2+ uptake and transport to all plant organs (Laszlo 1994;Storey and Leigh 2004;McGonigle and Grant 2015;Song et al 2018;Rosen et al 2019). However, data on comparing Ca 2+ and Sr 2+ uptake and translocation in tomato plants are scarce (Bowen H. J. M. and A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that Ca 2+ and Sr 2+ behave similarly in the biosphere and that most plants cannot discriminate between them at their biospheric concentrations (Watanabe et al 2007(Watanabe et al , 2016Drouet and Herbauts 2008;Burger et al 2019b). Therefore, Sr 2+ has been used as a long-and short-term tracer of Ca 2+ uptake and transport to all plant organs (Laszlo 1994;Storey and Leigh 2004;McGonigle and Grant 2015;Song et al 2018;Rosen et al 2019). However, data on comparing Ca 2+ and Sr 2+ uptake and translocation in tomato plants are scarce (Bowen H. J. M. and A.…”
Section: Discussionmentioning
confidence: 99%
“…Natural Sr 2+ isotopes are increasingly used as tracers of Ca 2+ in land and water ecosystems, mainly to characterise and monitor Ca 2+ cycles in the biosphere and lithosphere (Åberg et al 1990;Drouet et al 2005;Drouet and Herbauts 2008;Peek and Clementz 2012). Moreover, Sr 2+ is also used as a tracer of Ca 2+ uptake and its symplastic and apoplastic transport to various plant organs: to fruits, fruit pedicel and leaves (Storey and Leigh 2004;Song et al 2018;Rosen et al 2019); to roots (McGonigle and Grant 2015) and embryos during development (Laszlo 1994). Some studies have established the direct connection between Ca 2+ and Sr 2+ allocation to the level of cell types (Storey and Leigh 2004), while others assumed that Ca 2+ and Sr 2+ share transport and distribution pattern without validation (Song et al 2018;Rosen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation